Foundational research in accounting: professional memoirs and beyond - Mattessich, Richard (De Computis, Revista Española de Historia de la Contabilidad., 2006)
It was with particular pleasure that, several years ago, I accepted the invitation of Chuo University to write a professional, biographical essay about my own experience with accounting. My relation with this university is a long-standing one. Shortly after two of my books, Accounting and Analytical Methods and Simulation of the Firm Through a Budget Computer Program, were published in the USA in 1964, Professor Kenji Aizaki (then at Chuo University) and his former student, Professor Fujio Harada, and later other scholars from Chuo University, began actively promoting my ideas in Japan. And after a two volume Japanese translation of the first of these books was published in 1972 and 1975 (through the mediation of Professor Shinzaburo Koshimura, then President of Yokohama National University), my research found fertile ground in Japan through continuing efforts of three generations of accounting academics from Chuo University. I suppose it is thanks to these endeavours that my efforts became so well known in Japan, and that during some three decades many Japanese accounting professors contacted me either personally or by correspondence. Then from 1988 to 1990 Prof. Yoshiaki Koguchi, again from Chuo University, came as a visiting scholar to the University of British Columbia, audited some of my classes, and became a good friend and collaborator, which further strengthened my ties to this university.